TEKANAN KEPUNAHAN BAHASA SUWAWA: ANALISIS TINGKAT DAYA HIDUP BAHASA (THE PRESSURE OF EXTINCTION OF SUWAWA LANGUAGE: LANGUAGE LIFE-FORCE ANALYSIS) - winci Firdaus (Balai Bahasa Jawa Barat, 2018)
This study aims to determine the characteristics of respondents and Suwawa language vitality criterion based on the average value of the index with the characteristics of respondents. With reference to the purpose, this research is useful to serve as a source of information about the life-force of Suwawa language and can also be used as a material mapping the vitality of regional languages. The research method used is descriptive quantitative method. The measuring instrument used to analyze the Suwawa language vitality criterion is Likert scale model and index with compare mean test using SPSS 23 application. Analysis of the identification of Suwawa's vitality criteria can be determined by subindex group calculation with four respondent character variables, ie sex, group age, education level. Based on the results of data analysis Suwawa's vitality criteria are classified as Stable and steady, but are threatened with extinction.